Menentukan Variabel Prediktor bagi Kinerja Guru PAI - Ikhrom, Ikhrom (Nadwa, 2014)
This paper attempts to analyze the influence of supervision of Islamic Edu-cation (PAI), compensation, competence, and motivation to work on PAI teacher performance. The result of multiple linear regression analysis con-cluded that all four aspects are jointly significant affect the performance of teachers PAI. Partial regression test results explained that the supervision and competence of significant influence while compensation and motivation influenced but not significant. Based on the model test found that supervision direct impact on performance. Supervision has a direct influence scores greater than the indirect effect. Compensation does not affect the performance directly but through the direct influence of motivation because scores compensation is smaller than the indirect effect. Competence directly influen-ce performance significantly due to the direct influence of competence scores greater than the indirect effect scores.